Death of an era - Aw, Geok Kheng (2008)
This report traces the creation process of our project, it takes the form of a 20-minute video documentary. It traces the changes in the attitudes of Chinese Singaporeans towards funerals, in particular, the trend where more of them are choosing Buddhist funerals over Taoist funerals.